If f(x) = (2x+9)^3, f '(x) = 3(2x+9)^2*(2), or f '(x) = 6(2x+9)^2. Here we used the power rule with chain rule to find the derivative.
Answer:
The midpoint is (2 , 1)
Step-by-step explanation:
To find the midpoint, we have to add the corresponding coordinates
[(-5 , 3) + (3 , -1)] / 2
we separate into the corresponding
(-5 + 3) / 2 =
-2 / 2 = -1
(3 - 1) / 2 =
2 / 2 = 1
The midpoint is (2 , 1)
Answer:
Donna-71
Martina-62
Martina's sample
It has the smaller mean
Step-by-step explanation:
I apologize if this answer is incorrect but I think this is right.
Answer:
yes
Step-by-step explanation:
Given:
Kelly purchased 5 containers of ice cream for a party.
Each container holds 8 cups of ice cream.
Her brother ate 2 cups of ice cream.
One serving of ice cream = 2/3 of a cup.
To find:
Number of servings of ice cream will be left for the party?
Solution:
We have,
1 container = 8 cups of ice cream
5 containers = 5×8 = 40 cups of ice cream
Her brother ate 2 cups of ice cream. So, remaining cups of ice cream is
cups
Now,
of a cup = 1 serving
1 cup =
serving
38 cup =
serving
=
serving
= 57 serving
Therefore, 57 servings of ice cream will be left for the party.